Answer:
your answer should be d
Step-by-step explanation:
Answer:
How many plates are on the table as it results in only one value with no variability
Step-by-step explanation:
Answer:
(x-5)^2+(y+4)^2=100
Step-by-step explanation:
As we know the given points
Center = (5, -4)
and
Point on circle = (-3,2)
The distance between point on circle and center will give us the radius of circle
So,
The formula for distance is:
![\sqrt{(x_{2}-x_{1} )^{2}+(y_{2}-y_{1})^{2}}\\Taking\ center\ as\ point\ 1\ and\ the\ other\ point\ as\ point\ 2\\d=\sqrt{(-3-5)^{2}+(2-(-4))^{2}}\\d=\sqrt{(-8)^{2}+(2+4)^{2}}\\d=\sqrt{(-8)^{2}+(6)^{2}}\\\\d=\sqrt{64+36}\\d=\sqrt{100} \\ d=10\\So\ the\ radius\ is\ 10](https://tex.z-dn.net/?f=%5Csqrt%7B%28x_%7B2%7D-x_%7B1%7D%20%29%5E%7B2%7D%2B%28y_%7B2%7D-y_%7B1%7D%29%5E%7B2%7D%7D%5C%5CTaking%5C%20center%5C%20as%5C%20point%5C%201%5C%20and%5C%20the%5C%20other%5C%20point%5C%20as%5C%20point%5C%202%5C%5Cd%3D%5Csqrt%7B%28-3-5%29%5E%7B2%7D%2B%282-%28-4%29%29%5E%7B2%7D%7D%5C%5Cd%3D%5Csqrt%7B%28-8%29%5E%7B2%7D%2B%282%2B4%29%5E%7B2%7D%7D%5C%5Cd%3D%5Csqrt%7B%28-8%29%5E%7B2%7D%2B%286%29%5E%7B2%7D%7D%5C%5C%5C%5Cd%3D%5Csqrt%7B64%2B36%7D%5C%5Cd%3D%5Csqrt%7B100%7D%20%5C%5C%20d%3D10%5C%5CSo%5C%20the%5C%20radius%5C%20is%5C%2010)
The standard form of equation of circle is:
![(x-h)^{2}+(y-k)^{2}=r^{2}](https://tex.z-dn.net/?f=%28x-h%29%5E%7B2%7D%2B%28y-k%29%5E%7B2%7D%3Dr%5E%7B2%7D)
where h and k are the coordinates of the center. So putting in the value:
![(x-5)^{2}+(y-(-4))^{2}=(10)^{2}\\(x-5)^{2}+(y+4)^{2}=100](https://tex.z-dn.net/?f=%28x-5%29%5E%7B2%7D%2B%28y-%28-4%29%29%5E%7B2%7D%3D%2810%29%5E%7B2%7D%5C%5C%28x-5%29%5E%7B2%7D%2B%28y%2B4%29%5E%7B2%7D%3D100)
Answer:
The value of a = - 1 , And b =
Step-by-step explanation:
Given as :
Function f(x) = ![\frac{(x + a)}{(x + b)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%20%2B%20a%29%7D%7B%28x%20%2B%20b%29%7D)
And f(f(1)) = 0 And f(2) = - 3
Now For , x = 2 , y = - 3
I.e f(2) = ![\frac{(2 + a)}{(2 + b)}](https://tex.z-dn.net/?f=%5Cfrac%7B%282%20%2B%20a%29%7D%7B%282%20%2B%20b%29%7D)
or, - 3 =
I.e 2 + a = - 6 - 3b
Or, a + 3b = - 8 ....... 1
Again f(f(1)) = 0
So,
= 0
Or, 1 + a = 0
∴ a = - 1
So , put htis value of a i n eq 1 , we get value of b
So , - 1 + 3b = - 8
Or, 3b = - 7
∴ b =
Hence The value of a = - 1 , And b =
Answer